Transport Personnel Health Cohort (TRAPHEAC): study protocol and methodological considerations - Irina Guseva Canu; Viviane Fiona Mathilde Remy (Environmental Health and Preventive Medicine)
Background: Only prospective cohort studies can capture changes in work conditions and their effects on health. Such studies are rare in bus drivers, despite their high rates of injuries and diseases. The three existing cohorts have limited exposure data, collected at baseline and thus uninformative on exposure and exposure-effect dynamics. Therefore, we aimed to develop the Swiss Transport Personnel Health Cohort (TRAPHEAC) and to anticipate and prevent potential bias. Methods: To set up the study protocol, we first organized the stakeholder consultation and available data inventory. Second, we mapped the exposure-outcomes pairs to list the most prevalent occupational hazards, and conducted exposure measurement campaigns. Third, we built the Swiss Bus-Exposure Matrix for physical-chemical hazards and Bus-Ergonomics Matrix for visual and biomechanical constrains. These matrices contain 705 bus models operated in Switzerland since 1980 and enable assessing current and past exposure when merged with bus drivers’ work histories. Results: We opted for an original study design combining prospective cohort part starting at 2024 and a retrospective part with nested case-control studies. Bus drivers will be invited through three complementary channels: unions, companies, and social media. The eligibility screening, information, and consent form signature and registration will be conducted using the study web-site modules. Registered bus drivers will first receive a comprehensive inclusion questionnaire, then a yearly follow-up questionnaire to assess and update the drivers’ work histories. Validated self-reported questionnaires will be used for assessing additional health outcomes (e.g., stress, sleep problems, musculoskeletal disorders, burnout) and individual, occupational and live-style related factors (e.g., personality, ICT use, physical activity). Hospital records (with diagnosed diseases, diagnosis dates and treatments) centralized since 2000 by the Swiss Federal Statics Office will be used for assessing disease prevalence, incidence and case-control status. Advanced statistical analysis will be conducted to address etiological and methodological questions (e.g., individual and joint causal effects of multiple exposures and exposure components; time-varying exposure and outcome variables and confounders mixtures). Conclusions: The yearly assessment of both exposure and health outcomes should enable capturing changes in work conditions and their effects on bus drivers’ health and well-being over time and facilitate the tailoring, implementation and evaluation of preventive interventions.